Viewpoint: Hunger as a weapon of war: Hitler's Hunger Plan, Native American resettlement and starvation in Yemen. (April 2020) - Runge, Carlisle Ford; Graham, Linnea
Highlights: The Nazi Hunger Plan killed 4.2 million Soviets starved from 1941 to 1944. The Reich desperately believed in the imperative of territorial expansion. Hitler's starvation of Russia relied on the American history with "Redskins". The Hunger Plan links the crisis in Yemen to Nazi beliefs about the American West. Food is a core human right and hunger as a weapon of war is profoundly wrong. Abstract: This article will consider the Nazi Hunger Plan as an instrument of annihilation and tool of war, its retrospective reliance on the American example of resettlement of indigenous peoples, and how these policies prefigured the use of starvation against the people of Yemen by Saudi Arabia, aided and abetted by US and British foreign policy. It is part of a growing literature on state-induced famines.